Diagnosis and therapy of recurrent renal metastases after surgery for testicular seminoma: a rare case report and review of the literature - Zhuang Li; Zhuang Li; Yuanyuan Luo; Bo Yu; Hao Su; Dongbo Yuan; Jianguo Zhu; Jianguo Zhu (Frontiers in Oncology)
BackgroundSeminoma is a malignant tumor arising from testicular germ cells, with cryptorchidism recognized as a major risk factor for its development. Although retroperitoneal lymph node metastasis is common, renal metastasis is exceedingly rare. Testicular seminomas are generally highly sensitive to chemotherapy; however, the treatment and prognosis become significantly more challenging in cases of distant metastasis.Case presentationThis case report describes a 39-year-old male patient who unexpectedly discovered a left testicular seminoma following surgery but did not receive postoperative adjuvant chemotherapy due to personal reasons. Thirteen months after surgery, the patient was admitted for left-sided lumbar pain for 1 month. Abdominal enhanced CT imaging revealed a large renal tumor measuring 115 × 120 × 97 mm at the lower pole of the left kidney. The patient subsequently underwent a percutaneous biopsy of the left renal mass, and histopathological examination confirmed that the renal tumor originated from testicular seminoma. The patient then received four cycles of bleomycin, etoposide, and cisplatin (BEP) chemotherapy. Follow-up abdominal CT showed a reduction in the size of the left renal tumor to 56 × 45 × 60 mm, with several enlarged lymph nodes in the abdominal cavity and retroperitoneum (the largest approximately 10 mm in diameter). The patient eventually underwent “left nephrectomy and partial retroperitoneal lymph node dissection”. Postoperative histopathological analysis revealed no evidence of residual tumor cells. Shortly after surgery, the patient developed acute complete intestinal obstruction, which was treated surgically, and his condition improved significantly. The patient maintained clinical stability throughout the 4-month follow-up period without evidence of disease recurrence.ConclusionPostoperative adjuvant chemotherapy is essential for patients with testicular seminoma to minimize the risk of tumor recurrence and metastasis. In cases of renal metastasis from seminoma, salvage chemotherapy using the BEP regimen combined with nephrectomy may contribute to improved clinical outcomes.